Disability Sensitivity and Sensibility: A Nondisabled Lecturer Perspective on Inclusive Lecturing Opportunities - Sandra Makwembere (Research in Social Sciences and Technology, 2021)
Disability is a social force that arguably creates more education problems for students with disabilities than their impairments. Understanding it as a form of social oppression can lead to less exclusionary teaching and learning attitudes, beliefs, expectations and practices. Numerous studies have looked at the experiences of staff and students with disabilities as well as the experiences of teaching students with disabilities. However, more studies are needed to better understand and address disability in higher education. Nondisabled perspectives have a role to play in opposing disabling educational practices and cultures to make higher education more inclusive. Many opportunities especially exist for nondisabled lecturers to contribute to addressing the higher education barriers and discrimination which often affect students with disabilities. The purpose of this study was to use a disability perspective to present my lecturing practices during the move to emergency remote teaching and learning in response to COVID-19 while working at an HDI. An autoethnographic method was used. Content analysis of my accounts exposed the exclusionary nature of my practices in terms of how they facilitated ableism and suppressed disability discourse. Recommendations are made, in light of the results, on ways to not only make higher education spaces more accommodating but counter a wider societal culture that oppresses and even seeks to eradicate the value of those who live with impairments.